Assessment of phytochemicals, antioxidant properties, and in vivo antidiarrheal activity of date palm (Phoenix dactylifera L.) - Sadia Kharal; Farzana Siddique; Muhammad Arshad; Khansa Iftikhar; Muhammad Tahir Akhtar; Rahman Qadir; Manal Y. Sameeh; Muhammad Mustaqeem; Jinqiang Zhuang; Le Xia (International Journal of Food Properties)
Date palm (Phoenix dactylifera L.) has a significant role in our daily life due to its diverse nutritional composition and potential health benefits. This study was designed to evaluate the phytochemicals, antioxidant, and antidiarrheal potential of various extracts of Ajwa whole fruit, date palm pit, and flesh. The extracts with the highest phytochemical quantities were further subjected to bio-assay assessment against castor oil-induced diarrhea using different animal models. The results indicated that Ajwa whole fruit extract (AWFE) exhibited higher amount of total phenolic contents (TPC: 36 ± 16 mg/g GAE), total flavonoid contents (TFC: 360 ± 135 mg/g RE), and 2, 2-diphenyl-1-picrylhydrazyl (DPPH: 60 ± 7%) in hydro-ethanolic extracts. In vivo results revealed that Ajwa whole fruit 60% hydro-ethanolic extract at high dose (2000 mg/kg) showed significantly (p < .05) highest protective effect against diarrheal changes in mice. In case of AWFE, the intestinal contents % inhibition was slightly higher (72%) as compared to that of loperamide control (70%). High dose of Ajwa whole (2000 mg/kg) demonstrated less effectiveness (66 ± 11%) in comparison with loperamide (78 ± 8%) regarding % inhibition of fluid accumulation in enteropooling studies. High dose (2000 mg/kg) of Ajwa also reduced intestinal transit time by decreasing the % distance (53 ± 1%) in comparison with loperamide (57 ± 1%). The % inhibition of charcoal meal traveling of AWFE (38 ± 2%) was also significantly higher as compared to loperamide (26 ± 1%). The findings of the current study reveal that AWFE might be consumed as an ingredient in daily food products to counter effect the symptoms of diarrhea.